Stem Cell Therapy for Neurodegenerative Diseases - Ming Li; Susumu Ikehara (Studies on Stem Cells Research and Therapy - Peertechz Publications, 2015)
Stem cell therapy for neurodegenerative diseases Aging-related neurodegenerative disorders mainly include Alzheimer's disease (AD) and Parkinson's disease (PD). AD is the most common form of dementia, which is one of the major causes of disability and dependency in the elderly. Since the pathologic characteristics of AD are beta-amyloid (Abeta) plaques and neurofibrillary tangles (NFT) [1], depleting Abeta should be a useful therapy for AD. Extracellular Cathepsin B is associated with amyloid plaques, and colocalizes with Abeta in regulated secretory vesicles in chromaffin cells in AD brains. One report demonstrated that Cathepsin B reduces the relative abundance of Abeta through limited proteolysis, suggesting that the activation of Cathepsin B could offer a therapeutic strategy for AD [2]. Furthermore, antioxidants such as glutathione and vitamin E have been shown to be related to a reduced risk of AD resulting from a decrease in ROS levels, and protects against lipid peroxidation in the brain [3]. In contrast, PD is a chronic progressive disease, characterized by bradykinesia with tremors or postural instability. Its pathologic features show that dopaminergic neurons are lost in the mid-brain, associated with the activation of microglia [4]. Treatment of PD includes  medications such as those used in dopamine replacement therapy, dopamine agonists, and  anticholinergics, as well as exercise and physical therapy. All treatments aim to control symptoms but   cannot prevent the development of the disease.